AB0532 Oxidative stress and its related factors in patients with ankylosing spondylitis. (23rd January 2014) - Solmaz, D.; Kozacı, D.; Sari, I.; Güney, N.; Taylan, A.; Onen, F.; Akkoc, N.; Akar, S.
Abstract : Background: Ankylosing spondylitis (AS) is chronic inflammatory disease of the spine and sacroiliac joints with an unknown etiology. In recent years some researchers revealed an increased oxidative stress, which is thought to play an important role in the pathogenesis of some diseases, in AS. However, data regarding this subject is limited and additional studies are required. Objectives: The primary aim of this study was to investigate oxidative stress and related factors in AS. Methods: 85 AS patients, diagnosed according to the Modified New York criteria(mean age (36±10 years; 39M/17F) and 56 healthy subjects (36±10 years; 39M/17F) with no known CV risk factors including hypertension (HT), diabetes mellitus (DM), hyperlipidemia, and smoking were included in the study. Serum total oxidant status (TOS) and total anti-oxidant status (TAS) were studied. BASFI, BASDAI and BASMI were calculated. Disease duration and medications were noted. Logistic regression model was used to identify the independent risk factors for TOS. Results: There were no differences with respect to the age, sex distribution, waist circumferences, glucose, lipid and TAS concentrations between the patient and control groups. On the other hand, serum TOS levels were significantly higher in AS group than the controls (p=0.03). Comparison of active (BASDAI≥4) and inactive AS patients revealed that TOS were significantly higher in the active group (Table ). Subgroup analysis of patients with respect to the treatment revealed that TOS and TAS concentrations were not different between patients treated with biologics and conventional agents. Correlation analysis yielded significant correlations between TOS, TAS, BASMI, BASFI, BASDAI, ESR, CRP (p<0.05; r=0.291, r=0.451, r=0.271, r=0.363, r=0.456 and 0.437 respectively) and a positive correlation between TAS and BASMI (p<0.05; r=0.344).). In regression analysis, only BASMI and CRP were independently predicted the TOS levels (P<0.05). Conclusions: (1) There is an increased oxidative stress in AS patients compared with healthy subjects; (2) Patients with active disease had significantly higher oxidative stress compared with inactive patients and healthy controls; (3) Treatment status seems no effect on TOS; and (4) BASMI and CRP are the independent variables associated with TOS. Disclosure of Interest: None Declared